2014
DOI: 10.1002/acp.3083
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficacy of Security Screening Tasks: A Review of Visual Search Challenges and Ways to Mitigate Their Adverse Effects

Abstract: Security checkpoints are used to keep potentially dangerous items and individuals out of secure areas. Although technological advances can enhance security efficacy through both accuracy and speed, ultimate success or failure is largely determined by human performance. As such, it is necessary to minimize any shortcomings that stem from the limits of human cognitive abilities. Cognitive performance can be influenced by numerous factors, including those imposed by the search task (e.g., the number of prohibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…Thus decisionmaking is a key feature of the task; that is, not only "seeing" an incident, but interpreting its significance and determining an appropriate level of response. This continuous visual search for low-probability potential incidents shares some similarities with other surveillance tasks such as baggage screening or air traffic control, although there are also notable differences: Unlike the static screen shots used in luggage monitoring (see Biggs & Mitroff, 2015), urban security surveillance involves dynamic, evolving crowd scenes which place greater demands on visual Challenges of security surveillance 9 search processes; and unlike for example, an air traffic controller who observes and actively manipulates aircraft within a flight space (e.g., Metzger & Parasuraman, 2001), the job of a CCTV operator is passive with no interaction or influence over the movement of targets.…”
Section: The Task Of a Cctv Operatormentioning
confidence: 99%
“…Thus decisionmaking is a key feature of the task; that is, not only "seeing" an incident, but interpreting its significance and determining an appropriate level of response. This continuous visual search for low-probability potential incidents shares some similarities with other surveillance tasks such as baggage screening or air traffic control, although there are also notable differences: Unlike the static screen shots used in luggage monitoring (see Biggs & Mitroff, 2015), urban security surveillance involves dynamic, evolving crowd scenes which place greater demands on visual Challenges of security surveillance 9 search processes; and unlike for example, an air traffic controller who observes and actively manipulates aircraft within a flight space (e.g., Metzger & Parasuraman, 2001), the job of a CCTV operator is passive with no interaction or influence over the movement of targets.…”
Section: The Task Of a Cctv Operatormentioning
confidence: 99%
“…Due to the infrequency of drowning incidents, the visual search for such occurrences is challenging (Lanagan-Leitzel, Skow, & Moore, 2015). The difficulties involved in detecting infrequent drowning targets are reflected in other areas of real-world visual search with uncommon target items, such as airport security screenings (Biggs & Mitroff, 2015;Wolfe, Horowitz, & Kenner, 2005). For example, Wolfe et al (2005) found lowprevalence targets (occurring on 1% of trials) were missed more frequently than high-prevalence targets (occurring on 50% of trials), with error rates of 30% and 7% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although the comparison between groups remained statistically significant, these results would change some existing conclusions about this paradigm. In particular, this manipulation has yielded significant error rates in several published studies , 2015bCain et al, 2011;Fleck et al, 2010), yet those previous studies used variants of the baseline and weighted methods. In turn, the discrepancy raises the question as to whether significant SSM errors would have been observed in these previous studies with the dependent method.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent search accuracy thus improves without the need to maintain either the location or identity of the found target, which supports the idea that resource depletion is one of the primary factors contributing to SSM errors. Numerous situational factors can likewise affect SSM error rates, including anxiety (Cain, Dunsmoor, LaBar, & Mitroff, 2011), task structure (Clark, Cain, Adcock, & Mitroff, 2014), and decision-making criteria (Biggs & Mitroff, 2015b). However, these other factors can be generally aligned to support one or more of the three theoretical positions: satisfaction, perceptual bias, or resource depletion.…”
Section: Known Causes Of Multiple-target Search Errorsmentioning
confidence: 99%